Inferior Vena Cava Collapsibility as a Predictor of Mortality in Patients Admitted with Severe Acute Decompensated Heart Failure (Community Based Medical Journal, 2026)
Severe acute decompensated heart failure (ADHF) has a high mortality risk. Reliable, early prognostic tools are crucial. The predictive value of inferior vena cava (IVC) collapsibility, a non-invasive measure of volume status, for in-hospital mortality in specific populations, especially in resource-limited settings, requires further validation. Our objective was to evaluate whether bedside ultrasonographic assessment of IVC collapsibility index (IVC-CI) at admission is a significant predictor of in-hospital mortality among patients with severe ADHF. A prospective cohort study was conducted at Bangladesh Medical College Hospital from January 2024 to June 2025. Using purposive sampling, 80 consecutive patients admitted with severe ADHF were enrolled. IVC-CI was measured via transthoracic echocardiography within 24 hours of admission. Data were analyzed using SPSS version 23.0, employing receiver operating characteristic (ROC) curve analysis to determine the optimal IVC-CI cutoff and multivariate logistic regression to identify independent predictors of mortality. Among 80 enrolled patients, in-hospital mortality was 31.3% (25/80). Non-survivors had a significantly lower mean IVC-CI (28.4% ± 9.1 vs. 52.7% ± 12.3, p